The Profile of the Moroccan Entrepreneur: The New Generation of Entrepreneurs in Morocco - Cheikh, Boutayna Ibn; Alaoui, Lalla Latifa (European Scientific Journal, ESJ, 2018)
The present paper is the core of a study carried out based on a survey of 113 Moroccan entrepreneurs belonging to the new generation, not only because of its age (25-45 years), but also and especially in particular its citizens’ behavior, economic patriotism, investment in risk areas and contribution to the national effort of innovation, training and modernization of industrial relations. According to this study, we can understand the roots of the Moroccan elite, and the new economic elite in its relation to the stakes of the reform that has lived in modern Morocco, and analyze the mutations. Each criteria has been crowned by a series of testimonies collected from a sample of entrepreneurs and representatives of the general administration, although belonging to various geographical, ethnic, social and professional horizons, but most often animated by an only goal: to help build a winning Morocco. At the end of this study, We have sketched out a model of the new generation of entrepreneurs "The elitist entrepreneur." It would be pretentious to clarify the realities of entrepreneurship in Morocco are of great complexity.